NOISEtte CFD&CAA Supercomputer Code for Research and Applications - Abalakin, Ilya V.; Bakhvalov, Pavel A.; Bobkov, Vladimir G.; Duben, Alexey P.; Gorobets, Andrey V.; Kozubskaya, Tatiana K.; Rodionov, Pavel V.; Zhdanova, Natalia S. (Supercomputing Frontiers and Innovations, 2024)
The paper presents an overview of the CFD/CAA code NOISEtte. The code development began in the 2000s. At first it was a research code intended for elaboration of new methods and techniques in CFD and CAA. Nowadays NOISEtte is actively used as a means for solving numerically various applied problems in aviation industry, turbomachinery, helicopter manufacturing, and space rocket engineering. The code operates on mixed-element unstructured meshes, its numerical algorithm is built on higher-accuracy finite-volume methods using quasi-one-dimensional edge-based reconstruction of flow variables. It is well suited for simulating complex turbulent flows, and especially for high-fidelity scale-resolving simulation of non-stationary turbulent flows using novel RANS-LES methods. A remarkable feature of NOISEtte is its original parallel model, which allows computing with high efficiency on modern supercomputers with arbitrary architectures including CPU cores and GPU accelerators.